RESPONSIVITAS APARAT DESA DALAM PENYALURAN BANTUAN LANGSUNG TUNAI DI DESA TAENG KECAMATAN PALLANGGA KABUPATEN GOWA - Jumriana, Jumriana; Mone, Ansyari; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the responsiveness of village officials in the distribution of direct cash assistance in Taeng village, Pallangga district, Gowa Regency. The results of the study consist of six aspects, namely (1) the ability to respond to village officials related to administrative services and also the distribution of direct cash assistance at the Taeng village office. It has been seen successfully from the response of the community who received direct cash assistance in Taeng Village. (2 Village office applies a maximum of 5 minutes in carrying out services related to administrative services and also distributing direct cash assistance. (3 Accuracy in carrying out services carried out by Village officials related to direct cash assistance services and the right target recipients of direct cash assistance in Taeng Village. (4) Accuracy of Taeng village officials in providing services related to the distribution of direct cash assistance at the Taeng Village office (5) Accuracy time in providing services at the Taeng Village office in terms of administrative services and distribution of direct cash assistance because village officials immediately process so that the community does not wait too long and is convoluted (6) Ability to respond to complaints from the community